ChemInform Abstract: Crystal Structure of the Th2Ni10Al15 Phase Solved Using Electron Diffraction Tomography. Issue 9 (February 2016) - Yaniv, G.; Meshi, L.
Abstract: Intermetallic Th2 Ni10 Al15 is prepared by arc melting of the elements followed by homogenization annealing under Ar (Ta foil in quartz capsule, 800 °C, 4 weeks).